The Performance of ESG Investments During Financial Turmoil : Evidence from Finland - Hyvärinen, Pekka (My University, 2024)
Responsible investing, driven by legislation and growing consumer awareness, has gained prom-inence. This study investigates whether integrating sustainability into investment strategies yields superior returns during market turmoil like the Covid-19 pandemic and the Russia-Ukraine war. Focusing on markets, it evaluates whether Finnish ESG funds outperform market indices from 2020 to 2024. Utilizing event study methodology, the research assesses the performance of Finnish ESG funds against Finnish benchmarks during economically unstable periods. Recent studies categorize findings on responsible investing, highlighting potential for superior returns and lower volatility in funds with higher ESG ratings. Discrepancies arise regarding re-sponsible investing's impact during downturns, with some studies suggesting outperformance and others indicating no significant difference compared to conventional funds. Regional effects and varying methodologies contribute to these disparities. Despite mixed findings, responsible investing garners attention as investors balance financial returns and ethical considerations. This empirical study focuses on Finnish ESG funds' performance during financial turmoil, using data from the Morningstar database. Morningstar's sustainability ratings, based on Sustainalyt-ics' ESG scores, inform the analysis of funds' environmental, social, and governance criteria. Among 67 Finnish equity funds initially considered, a subset of 20 funds with globe sustainability ratings is selected. The study compares their performance against the OMX Helsinki GI index over four years, highlighting ESG funds' outperformance during challenges like the Covid-19 pan-demic and the Russia-Ukraine war. Methodological constraints, including assumptions about fund performance and crisis impact periods, are carefully addressed to ensure validity. By analyzing cumulative abnormal returns (CARs) and conducting statistical tests, this study con-firms ESG funds' outperformance, particularly during the Covid-19 pandemic. However, they slightly underperform the benchmark index during the whole four-year sample period. The ESG funds also underperform the benchmark index during the initial year following the Russia-Ukraine war, reflecting sensitivity to geopolitical events. The findings support sustainable invest-ment strategies' resilience and superior returns during financial turmoil, aligning with previous research. Despite sample size limitations, the study underscores the importance of sustainable finance and suggests avenues for future research to refine methodologies and enhance under-standing.

Vastuullinen sijoittaminen, jota ohjaa lainsäädäntö ja kasvava kuluttajatietoisuus, on saanut merkittävän aseman viime vuosikymmenenä. Tässä tutkimuksessa selvitetään, tuottaako kestä-vyyden integroiminen sijoitusstrategioihin parempia tuottoja markkinoiden myllerryksissä, ku-ten Covid-19-pandemian ja Venäjä-Ukraina-sodan aikana. Painopisteenä ovat suomalaiset mark-kinat, ja tutkimuksessa arvioidaan, ylittävätkö ESG-rahastot markkinaindeksit vuosina 2020–2024. Hyödyntämällä ”event study” menetelmää tutkimus arvioi ESG-rahastojen suoritusta suh-teessa vertailuindeksiin taloudellisesti epävakailla ajanjaksoilla. Viimeaikaiset tutkimukset luokittelevat vastuullisen sijoittamisen löydökset, korostaen mahdol-lisuutta parempiin tuottoihin ja alhaisempaan volatiliteettiin rahastoissa, joilla on korkeammat ESG-luokitukset. Eroavaisuuksia esiintyy vastuullisen sijoittamisen vaikutuksessa laskusuhdan-teissa, joissa jotkut tutkimukset viittaavat ylivoimaiseen suoritukseen ja toiset osoittavat, ettei merkittävää eroa ole verrattuna perinteisiin rahastoihin. Alueelliset vaikutukset ja vaihtelevat menetelmät vaikuttavat näihin eroihin. Sekavista löydöksistä huolimatta vastuullinen sijoittami-nen herättää huomiota, kun sijoittajat tasapainottavat taloudellisia tuottoja ja eettisiä näkökoh-tia. Tämä empiirinen tutkimus keskittyy suomalaisten ESG-rahastojen suoritukseen taloudellisen myllerryksen aikana, hyödyntäen tietoja Morningstar-tietokannasta. Morningstarin kestävyys-luokitukset, jotka perustuvat Sustainalyticsin ESG-pisteisiin, ohjaavat rahastojen ympäristö-, so-siaalisten ja hallinnollisten kriteerien analyysiä. Alun perin harkitusta 67 suomalaisesta osakera-hastosta valitaan 20 rahastoa. Tutkimus vertailee niiden suoritusta OMX Helsinki GI -indeksiin neljän vuoden ajanjakson aikana, korostaen ESG-rahastojen ylivoimaa haasteiden kuten Covid-19-pandemian ja Venäjä-Ukraina-konfliktin aikana. Tutkimukseen vaikuttavat rajoitteet on har-kittu huolellisesti varmistaakseen tulosten pätevyyden. Tutkimus vahvistaa suomalaisten ESG-rahastojen markkinaindeksiä paremman suoriutumisen, erityisesti pandemian aikana, analysoimalla kumulatiivisia poikkeamatuottoja (CAR) ja suoritta-malla tilastollisia testejä. Ne kuitenkin alisuoriutuvat ensimmäisenä vuotena Venäjä-Ukraina-konfliktin jälkeen, heijastaen herkkyyttä geopoliittisille konflikteille. Tulokset tukevat kestävien sijoitusstrategioiden kestävyyttä ja parempia tuottoja lyhyellä aikajänteellä, mikä on linjassa aiempien tutkimusten kanssa. Vaikka tutkimuksen rajoitukset otetaan huomioon, niin silti tutki-mus korostaa vastuullisen rahoituksen merkitystä ja tulevaisuuden tutkimuksen kannalta koros-taa entistä tarkempia rajauksia, jossa näyte koko voisi olla isompi ja muuttuva lainsäädäntö huo-mioon ottaen.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance